Etude du comportement mécanique des bétons autoplaçants confinés par des grilles composites - Belkacem, Bilal; Djilali Ben Fredje, Youcef; Benabed, Benchaa, Directeur de thèse; Boukhalkhal, Aboubaker, Directeur de thèse (My University, 2019)
This work consists of an experimental and analytical analysis of a new technique of confinement of self-compacting concrete cylinders by composite grids arranged circumferentially all along the periphery of the cylinder and totally integrated into the concrete matrix. The main objective is to quantify the resistance and deformation contribution that confinement can give to columns and its influence on the uniaxial compression failure mode. Nine mixtures of Self compacting concrete (SCC) have been prepared, including one reference (unconfined BAP) and eight with different types of grids (plastic, metallic and vegetable) with different shape of mesh (lozenge, square and triangle) . The formulation parameters namely Water / Binder and Superplasticizer/Binder were selected 0.4 and 0.9%, respectively. The tested specimens are cylindrical and have dimensions of 16 * 32cm. The results obtained show that it is possible to substantially increase the ductility of the columns, and in some cases their strength. It was also found during the compressive test that the failure mode of the confined self-compacting concrete is very influenced by the presence of the grids. The comparison of the experimental results with the analytical results gave a good concordance
Laghouat : Université Amar Telidji - Département de génie civil Option : Structures